Post-LBO Development Analysis of Changes in Strategy, Operations, and Performance after the Exit from Leveraged Buyouts in Germany - Lenz, Richard K.; SpringerLink (Online service) (Wiesbaden : Gabler, 2010)
The current financial crisis has intensified the discussion around buyouts and the related value creation of financial investors. Richard K. Lenz analyses how LBOs evolve after the financial investors have exited. Based on three case studies of former LBOs in Germany, he shows that performance decline is often related to the weakening of the former performance-enhancing series of governance instruments. The author reveals that management starts to over-emphasize growth while improvements on the micro-level of the company are robust and allow outperforming competitors. Finally, he concludes that performance decline seems to be rather due to inconsistent interests and less monitoring by new shareholders than to wealth transfer towards financial investors.
and Founding Theory -- Model Building and Hypotheses Development -- Empirical Part -- Synthesis and Outlook.
Keywords: Economics; Banks and banking; Economics/Management Science; Finance /Banking.